PENGARUH KOMPENSASI TERHADAP KINERJA GURU DI SMP NEGERI 3 BATUSANGKAR - Pitri, Alisyah (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2017)
This study aimed at determining the influence of compensation on teachersâ performance in State Secondary School 3 Batusangkar. The method used was a quantitative. The population in this study were all teachers of civil servants in State Secondary School 3 Batusangkar which consist of 43 people. Analyzer used in this research was simple linear regression, coefficient of determinant, and t test. Data processing using SPSS statistics 20 for windows. Based on the results of the study, it was known that simultaneously the compensation has a significant and positive effect on teachersâ performance. The result from simple linear that constant score equal to 100,008 and coefficient score of compensation equal to 0,378 this indicate that there is significant and positive influence to teachersâ performance in State Secondary School 3 Batusangkar. The result of determinant coefficient can be seen that the involvement of compensation variable to teachersâ performance is 17,1%. Result of t-test where t-count > t-table (2,905> 2,701) or sig. <0,01 (0,000 <0,01) which means that Ha is accepted and Ho is rejected. Â Keywords: Compensation, Teachersâ Performance, State Secondary School 3 Batusangkar